2007
DOI: 10.1158/0008-5472.can-06-1147
|View full text |Cite
|
Sign up to set email alerts
|

c-Met Overexpression Is a Prognostic Factor in Ovarian Cancer and an Effective Target for Inhibition of Peritoneal Dissemination and Invasion

Abstract: The hepatocyte growth factor receptor c-Met is a receptor tyrosine kinase that plays an important role in tumor growth by activating mitogenic signaling pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
259
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 242 publications
(269 citation statements)
references
References 38 publications
8
259
1
1
Order By: Relevance
“…To test this, we examined a set of inhibitors at effective concentrations that specifically inhibit various RTKs, including general RTKs (genistein), IGF-1R (AG1024), fibroblast growth factor receptor 1 (SU5402), epidermal growth factor receptor (EGFR) (AG1478) and hepatocyte growth factor receptor c-Met (K252a), which have been previously implicated in the progression and metastasis of ovarian cancer (Ellerbroek et al, 2001;Steele et al, 2001;Brokaw et al, 2007;Sawada et al, 2007). Among these inhibitors, we found that only genistein used to block RTK or AG1024 used to inhibit IGF-1R led to a marked decrease in p120 ctn activation ( Figure 3a) and translocation ( Figure 3b) following GnRHa stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…To test this, we examined a set of inhibitors at effective concentrations that specifically inhibit various RTKs, including general RTKs (genistein), IGF-1R (AG1024), fibroblast growth factor receptor 1 (SU5402), epidermal growth factor receptor (EGFR) (AG1478) and hepatocyte growth factor receptor c-Met (K252a), which have been previously implicated in the progression and metastasis of ovarian cancer (Ellerbroek et al, 2001;Steele et al, 2001;Brokaw et al, 2007;Sawada et al, 2007). Among these inhibitors, we found that only genistein used to block RTK or AG1024 used to inhibit IGF-1R led to a marked decrease in p120 ctn activation ( Figure 3a) and translocation ( Figure 3b) following GnRHa stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, mis-regulation of the HGF/cMET pathway has been investigated in ovarian cancer, and high expression of cMET has been identified in subsets of all four major histotypes of EOC (high grade serous, clear cell, mucinous, and endometrioid [22][23][24][25][26][27][28][29]). It must be noted, however, that the outcome from this over-expression remains unclear.…”
Section: Hgf/cmet In Ovarian Cancermentioning
confidence: 99%
“…It must be noted, however, that the outcome from this over-expression remains unclear. While several studies have demonstrated a correlation between high cMET expression and poor prognosis [25,30], others have shown no statistically significant correlation between cMET expression and shorter survival [26,29], and still others suggest that cMET is expressed in early tumours, and is associated with good prognostic factors [23]. It should be noted that the majority of these studies were performed on relatively small numbers of samples, and usually contained mixed subtypes of EOC, thus further confusing the matter.…”
Section: Hgf/cmet In Ovarian Cancermentioning
confidence: 99%
See 2 more Smart Citations